The Position of the Village Regulations in the Legal System in Indonesia - Isnaini, Enik; M. Yanto; Ramadlan, Muhammad Andika (Universitas Islam Lamongan, 2025)
ABSTRACT One of the principles of the rule of law is that governance must be based on the provisions of laws and regulations, including governance in villages must be implemented based on Village Regulations. Village Regulations are legal products in the village that are stipulated by the Village Head with the approval of the Village Consultative Body (BPD). As a legal product of the village, Village Regulations are used as the basis for organizing village governance. The type of research conducted is normative juridical with a statutory approach and a conceptual approach. The position of village regulations based on the provisions of Article 8 paragraphs (1) and (2) of Law Number 12 of 2011, is one type of statutory regulation, and its existence is recognized. And has binding legal force as long as it is ordered by higher statutory regulations or formed based on authority. The implementation of village governance must be implemented based on Village Regulations and other statutory regulations. Village regulations are formed as the basis for organizing village governance, one of which concerns the Village Revenue and Expenditure Budget (APBDes) which must be stipulated by Village Regulations. Village regulations are formed to be used as the basis for implementing development and implementing activities. others in the village so that Village Regulations exist in the implementation of village governance.